Reduced blood-brain barrier penetration of acne vulgaris antibiotic sarecycline compared to minocycline corresponds with lower lipophilicity - Grada, Ayman; Del Rosso, James Q.; Moore, Angela Y.; Stein Gold, Linda; Harper, Julie; Damiani, Giovanni; Shaw, Katharina; Obagi, Sabine; Salem, Raidah J.; Tanaka, S. Ken; Bunick, Christopher G. (Frontiers in Medicine, 2022)
Background: Vestibular side effects such as dizziness and vertigo can be a limitation for some antibiotics commonly used to treat acne, rosacea, and other dermatology indications. Objective: Unlike minocycline, which is a second-generation tetracycline, sarecycline, a narrow-spectrum third-generation tetracycline-class agent approved to treat acne vulgaris, has demonstrated low rates of vestibular-related adverse events in clinical trials. In this work, we evaluate the brain-penetrative and lipophilic attributes of sarecycline in 2 nonclinical studies and discuss potential associations with vestibular adverse events. Methods: Rats received either intravenous sarecycline or minocycline (1.0 mg/kg). Blood-brain penetrance was measured at 1, 3, and 6 hours postdosing. In another analysis, the lipophilicity of sarecycline, minocycline, and doxycycline was measured via octanol/water and chloroform/water distribution coefficients (logD) at pH 3.5, 5.5, and 7.4. Results: Unlike minocycline, sarecycline was not detected in brain samples postdosing. In the octanol/water solvent system, sarecycline had a numerically lower lipophilicity profile than minocycline and doxycycline at pH 5.5 and 7.4. Conclusion: The reduced blood-brain penetrance and lipophilicity of sarecycline compared with other tetracyclines may explain the low rates of vestibular-related adverse events seen in clinical trials.